Pengaruh Norma HAM Terhadap Proses Kemerdekaan Timor Leste dari Indonesia - Ardli Johan Kusuma (Department of Government Studies Universitas Muhammadiyah Makassar, 2017)
This paper discusses about the reasons of Indonesia which provides a referendum to East Timor which resulted in East Timor being independent from Indonesia. This paper is analytical descriptive, using qualitative methods, with the data collection techniques, using